Cm-Wavelength Observations of Mwc 758 Resolved Dust Trapping in a Vortex - Carcamo-Vasquez, M (Oxford University Press, 2019)
The large crescents imaged by ALMA in transition discs suggest that azimuthal dust trapping concentrates the larger grains, but centimetre–wavelengths continuum observations are required to map the distribution of the largest observable grains. A previous detection at ∼1 cm of an unresolved clump along the outer ring of MWC 758 (Clump 1), and buried inside more extended sub-mm continuum, motivates followup VLA observations. Deep multiconfiguration integrations reveal the morphology of Clump 1 and additional cm-wave components that we characterize via comparison with a deconvolution of recent 342 GHz data (∼1 mm). Clump 1, which concentrates ∼1/3 of the whole disc flux density at ∼1 cm, is resolved as a narrow arc with a deprojected aspect ratio χ > 5.6, and with half the azimuthal width than at 342 GHz. The spectral trends in the morphology of Clump 1 are quantitatively consistent with the Lyra-Lin prescriptions for dust trapping in an anticyclonic vortex, provided with porous grains (f ∼ 0.2 ± 0.2) in a very elongated (χ ∼ 14 ± 3) and cold (T ∼ 23 ± 2 K) vortex. The same prescriptions constrain the turbulence parameter α and the gas surface density g through log10 α × g/g cm−2 ∼ −2.3 ± 0.4, thus requiring values for g larger than a factor of a few compared to that reported in the literature from the CO isotopologues, if α 10−3. Such physical conditions imply an appreciably optically thick continuum even at cm-wavelengths (τ33 GHz ∼ 0.2). A secondary and shallower peak at 342 GHz is about twice fainter relative to Clump 1 at 33 GHz. Clump 2 appears to be less efficient at trapping large grains. © 2018 The Author(s)